2019
DOI: 10.1007/s11356-019-07305-1
|View full text |Cite
|
Sign up to set email alerts
|

Scheelite weathering and tungsten (W) mobility in historical oxidic-sulfidic skarn tailings at Yxsjöberg, Sweden

Abstract: More knowledge of the geochemical behavior of tungsten (W) and associated contamination risks is needed. Therefore, weathering of scheelite (CaWO 4) and secondary sequestration and transport of W to groundwater in historical skarn tailings and surface water downstream of the tailings were studied. The tailings contained 920 mg/kg W, primarily in scheelite. Mineralogical and geochemical analyses were combined to elucidate the geochemical behavior of W in the tailings, and water samples were taken monthly during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Even though the Wenzel's SEP is the most used for tungsten, it is not the only one. A different sequential extraction has been used to define tungsten speciation in mining soils [59]. This procedure, originally used by Dold [60], subdivided tungsten forms into seven fractions: (1) poly-tungstates water-soluble phase, (2) exchangeable phase, (3) easily reducible minerals, (4) resistant reducible minerals, (5) easily oxidizable minerals, (6) resistant oxidizable minerals, and (7) residues and silicates.…”
mentioning
confidence: 99%
“…Even though the Wenzel's SEP is the most used for tungsten, it is not the only one. A different sequential extraction has been used to define tungsten speciation in mining soils [59]. This procedure, originally used by Dold [60], subdivided tungsten forms into seven fractions: (1) poly-tungstates water-soluble phase, (2) exchangeable phase, (3) easily reducible minerals, (4) resistant reducible minerals, (5) easily oxidizable minerals, (6) resistant oxidizable minerals, and (7) residues and silicates.…”
mentioning
confidence: 99%
“…On the other hand, Al, Be, Ca, Sr, SO 4 2− and W concentrations range from 0.05-37 mg/L, 1-4671 μg/L, 498-642 mg/L, 168-242 μg/L, 455-639 mg/L and 0.5-24 μg/L, respectively. The (Hällström et al, 2019). The high pH in the groundwater despite the influence of sulphide oxidation is due to the relatively high carbonate (calcite) content (~6%) of the tailings.…”
Section: Hydrochemical Parametersmentioning
confidence: 99%
“…Previous ground and surface water sampling campaigns in the tailings and downstream, respectively (e.g. Höglund et al, 2004;Hällström et al, 2019), reported of W and other elemental contamination in some of the surface waters. These authors hypothesised that the groundwater from the tailings could be the source of these contaminants to the surface waters.…”
Section: Introductionmentioning
confidence: 96%
“…Liu et al found that Cu, Zn, and Cd were the main pollutants in the sediment around the copper mine areas [13]. Lina et al found that higher concentrations of particulate tungsten were found in the surface water downstream of a scheelite tailings pond [14]. The oxidation of sulfide tailings was the source of the mine environmental pollution [15,16].…”
Section: Introductionmentioning
confidence: 99%